More than just lower wages: intrinsic job quality for college graduates with disabilities. Issue 5 (17th August 2020) - Henly, Megan; Brucker, Debra L.
ABSTRACT: Americans with a disability are substantially less likely to be employed than those without a disability. Among those with a disability who are employed, additional layers of inequality have been established, including wage differences and access to benefits. Education is generally viewed as a pathway to professional work with good wages, benefits, and work conditions. In this paper, we utilise data from the 2017 National Survey of College Graduates, a nationally-representative sample of college graduates in the United States, to examine job quality between workers with and without a disability (n = 64, 998 between ages 20–64). In addition to economic characteristics where we observe a median wage gap of $6, 400 USD by disability status among full-time workers, this paper examines intrinsic qualities of work: autonomy, powerfulness, self-fulfilment, and meaningfulness of work. While college graduates generally rank high on intrinsic work quality (75% or more possess each of these qualities regardless of disability), on three of these four measures, full-time workers with a college degree and a disability scored significantly lower than their counterparts with no disability. We also consider individual-level preferences for job attributes and, after controlling for demographic characteristics, found that differences in intrinsic job quality by disability status remain.